Drinking Water Factors and Stunting Among Children Under Five in Konawe Islands Regency - Eka Ermawan; Erwin Azizi Jayadipraja; Sartini Risky (Waluya The International Science of Health Journal, 2026)
Introduction: Stunting remains a major nutritional problem affecting children's growth and development and contributes to the quality of human resources. The prevalence of stunting in several community health centers in Konawe Islands Regency remains high. This study aimed to analyze the relationship between drinking water factors (source, treatment, and physical quality) and the incidence of stunting among children under five years old. Method: This study used a quantitative approach with a cross-sectional design. The population consisted of 1,125 toddlers, and 89 respondents were selected using simple random sampling. Data were analyzed using the Chi-Square test, correlation test, and binary logistic regression. Result: The Chi-Square test results showed a significant relationship between drinking water sources and stunting (p=0.000), drinking water treatment and stunting (p=0.000), and drinking water quality and stunting (p=0.000) with correlation coefficient φ = 0.396. Conclusion: Drinking water factors, including water source, treatment, and physical quality, are significantly associated with the incidence of stunting among children under five in Konawe Islands Regency.